Brief Report: Two Day-Date Processing Methods in an Autistic Savant Calendar Calculator. - De Marco, Matteo; Iavarone, Alessandro; Santoro, Giovanna; Carlomagno, Sergio (Journal of Autism & Developmental Disorders, 2016)
Special ability in computing the day of week for given dates was observed in a 24 year-old male (FB) diagnosed with Asperger syndrome. FB performed almost flawlessly (98.2 %) both with past and future dates, over a span of 40 years. Response latency was slower as temporal remoteness of future dates increased. Within the future timespan, FB's performance was consistent with the active use of calendar regularities. On the contrary, within the past timespan (for which no remoteness effect was seen), his performance was mainly linked to memory retrieval of personal events. The case presented here complements the existent literature on calendar calculators, as, for first time, two distinct day-date processing styles are described in the same individual.